Q -anisotropy in finely-layered media - Picotti, Stefano (2010)
Finely-layered media behaves as a transversely isotropic medium at long wavelengths. If the constituent media are anelastic, Q-anisotropy is described by Postma averaging for two periodic layers and by Backus averaging for an stationary sequence of many layers. In order to test the theory, we perform numerical simulations of wave propagation in a periodic sequence of sandstone and limestone and compute the Q-factor of qP waves as a function of the propagation direction.